The influence of parenting behaviour and social support on parenting stress and behavioural problems of autistic children: a conceptual study within the Malaysian context - Damanhuri, Rokhwatun Nisa (IIUM Press, 2022)
Parents with ASD children reported experiencing a high level of parenting stress due to extra parenting demands when parenting their children. Studies have reported that parenting stress influences child behaviour problems; however, there are inconsistent research findings on the relationship. This is mainly due to the role of third variables (i.e., parenting behaviour and social support) that reveals variability in the research findings. These inconsistent findings have encouraged researchers to further investigation for the role of parenting behaviour and social support in the relationship between parenting stress and child behaviour problems. This paper aims to propose an empirical conceptual framework that investigates the role of parenting behaviour in mediating the relationship between parenting stress and autistic children’s behavioural problems and the moderating role of social support in mitigating the effect of parenting stress on parenting behaviour in the Malaysian context, as there are only a handful of studies that conducted such a relationship outside the Western context.